Cost-effectiveness analysis of public-private mixed models in national tuberculosis program in Ho Chi Minh City, Vietnam - Tran Nhat Quang (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2012